Simultaneous suppression of noise and reverberation in cochlear implants using a ratio masking strategy - Hazrati, Oldooz (Acoustical Society of America, 2013)
Cochlear implant (CI) recipients' ability to identify words is reduced in noisy or reverberant environments. The speech identification task for CI users becomes even more challenging in conditions where both reverberation and noise co-exist as they mask the spectro-temporal cues of speech in a rather complementary fashion. Ideal channel selection (ICS) was found to result in significantly more intelligible speech when applied to the noisy, reverberant, as well as noisy reverberant speech. In this study, a blind single-channel ratio masking strategy is presented to simultaneously suppress the negative effects of reverberation and noise on speech identification performance for CI users. In this strategy, noise power spectrum is estimated from the non-speech segments of the utterance while reverberation spectral variance is computed as a delayed and scaled version of the reverberant speech spectrum. Based on the estimated noise and reverberation power spectra, a weight between 0 and 1 is assigned to each time-frequency unit to form the final mask. Listening experiments conducted with CI users in two reverberant conditions (T(60) = 0.6 and 0.8 s) at a signal-to-noise ratio of 15 dB indicate substantial improvements in speech intelligibility in both reverberant-alone and noisy reverberant conditions considered.